In defense of the use of peripherally inserted central catheters in pediatric patients. Issue 3 (May 2021) - Crocoli, Alessandro; Cesaro, Simone; Cellini, Monica; Rossetti, Francesca; Sidro, Luca; Pinelli, Fulvio; Pittiruti, Mauro
Central venous access devices have revolutioned the care of children affected by malignancies, facilitating management of complex and prolonged infusive therapies, reducing pain and discomfort related to repeated blood samples and indiscriminate venipunctures, thus reducing also psychological stress of both patients and families. In this respect, peripherally inserted central catheters have been disseminated for use, even in pediatric oncology patients, for their many advantages: easy and non-invasive placement with no risk of insertion-related complications, as well as easy removal; reduced need for general anesthesia both for insertion and removal; adequate prolonged performance also for challenging therapies (e.g. stem cell transplantation); and low rate of late complications. Nonetheless, concerns have been recently raised about use of such devices in children with cancer, especially regarding a presumed (but not demonstrated) high risk of catheter-related venous thrombosis. Are we facing a new witch (or peripherally inserted central catheter) hunt? The choice of the central venous access device—particularly in oncologic children—should be based on an evaluation of clinical advantages and risks, as provided by appropriate and scientifically accurate clinical studies.